Decreasing adhesions and avoiding further surgery in a pediatric patient involved in a severe pedestrian versus motor vehicle accident - Amanda D. Rice; Leslie B. Wakefield; Kimberley Patterson; Evette D'Avy Reed; Belinda F. Wurn; C. Richard III King; Lawrence J. Wurn (MDPI AG, 2014)
In this case study, we report the use of manual physical therapy in a pediatric patient experiencing complications from a life-threatening motor vehicle accident that necessitated 19 surgeries over the course of 12 months. Post-surgical adhesions decreased the patient's quality of life. He developed multiple medical conditions including recurrent partial bowel obstructions and an ascending testicle. In an effort to avoid further surgery for bowel obstruction and the ascending testicle, the patient was effectively treated with a manual physical therapy regimen focused on decreasing adhesions. The therapy allowed return to an improved quality of life, significant decrease in subjective reports of pain and dysfunction, and apparent decreases in adhesive processes without further surgery, which are important goals for all patients, but especially for pediatric patients.